A vector-based approach to modeling knowledge in economics - Tim Sievers (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2005)
This paper draws attention to two important characteristics of knowledge which so far have been left unexplored, and proposes a new method to capture them in economic modeling with the help of vectors. The direction of the vector represents the knowledge's complementarity with other knowledge and its norm represents its potential economic value.
Keywords: C0; O3; 330; knowledge; innovation; innovative production; vector representation; complementarity